PELAYANAN PUBLIK DALAM KONTEKS PEMENUHAN KEBUTUHAN DASAR MASYARAKAT - Agus Rianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2018)
The service image is said to be important because it is the overall impression that isformed in the minds of the public about the public services provided by the villageapparatus. Community service can be categorized effectively if the community gets theease of service with a short, fast, appropriate and satisfying procedure. Most oftencomplained by residents of Klangenan Village is a guarantee of timely service processessuch as making E-KTP and others. This study aims to determine the Public Service Imagein Klangenan Village, Klangenan District, Cirebon Regency.Keywords: Image, Public Service, E-KTP